2021
DOI: 10.1681/asn.2021070966
|View full text |Cite
|
Sign up to set email alerts
|

B and T Cell Responses after a Third Dose of SARS-CoV-2 Vaccine in Kidney Transplant Recipients

Abstract: Background: Accumulating evidence suggests that solid organ transplant recipients, as opposed to the general population, show strongly impaired responsiveness towards standard SARS-CoV-2 mRNA-based vaccination, demanding alternative strategies for protection of this vulnerable group. Methods: In line with recent recommendations, a third dose of either heterologous ChAdOx1 (AstraZeneca) or homologous BNT162b2 (BioNTech) was administered to 25 kidney transplant recipients (KTR) without humoral response after 2 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
94
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 26 publications
17
94
4
1
Order By: Relevance
“… 109 110 111 112 113 In addition, 11 studies reporting seroconversion data of a third vaccine dose were included for qualitative analysis (see supplementary table 5). 43 114 115 116 117 118 119 120 121 122 123 One study was included in both meta-analysis and qualitative analysis of a third vaccine dose. 43 Five studies that met the inclusion criteria for meta-analysis were excluded because missing data could not be obtained in time from the corresponding authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 109 110 111 112 113 In addition, 11 studies reporting seroconversion data of a third vaccine dose were included for qualitative analysis (see supplementary table 5). 43 114 115 116 117 118 119 120 121 122 123 One study was included in both meta-analysis and qualitative analysis of a third vaccine dose. 43 Five studies that met the inclusion criteria for meta-analysis were excluded because missing data could not be obtained in time from the corresponding authors.…”
Section: Resultsmentioning
confidence: 99%
“…Ten prospective observational studies and one randomised controlled trial reported data after a third dose of covid-19 vaccine. Most of the studies (8/11 studies) were on organ transplant recipients, 115 116 117 118 119 120 121 122 with one study each on patients with immune mediated inflammatory disorders, 123 haematological cancers, 114 and solid cancers. 43 Nine studies utilised only mRNA vaccines (mRNA-1273 or BNT162b2), whereas two studies 114 121 administered either BNT162b2 or AZD1222 as a third dose after two doses of BNT162b2.…”
Section: Resultsmentioning
confidence: 99%
“…In solid organ transplant recipients, immunosuppressive drug number and type are major risk factors of seroconversion failure (34). As a significant proportion of solid organ transplant recipients still has impaired seroconversion rates even after a third mRNA vaccine dose, individualized vaccine protocols seem necessary for these vulnerable patients and vaccination prior to transplantation appears mandatory (18,(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, administration of a third dose of the vaccine was not efficient in patients on belatacept therapy (140). Importantly, the third vaccine dose increased not only Ab titers but also spike-reactive B and CD4 + T cells (141).…”
Section: Third Vaccine Dosesmentioning
confidence: 99%